Bridging the Gap between Brazilian Startups and Business Processes – Process Thinking’s Initial Exploratory Case Study - Magdaleno, Andrea Magalhaes; Engiel, Priscila; Tavares, Rafael Lage; Pisa, Pedro Silveira; Araujo, Renata Mendes (iSys - Journal of Information Systems, 2017)
Startup is a new business segment that has been growing up in the last years. These companies have an innovative spirit and are usually searching for new solutions to real problems that can be transformed into scalable businesses. The majority of these companies are not aware of their processes and how the company need to be organized. For this kind of companies, we propose Process Thinking, an innovative approach that makes the business process management viable in the daily lives of startups. This paper presents the Process Thinking framework, which prescribes 10 main processes that a startup needs and a utility belt to help the startup to organize their processes. We illustrate this proposal through an exploratory case study with a real IT startup company that used a 5-step methodology in an immediate implementation of proposed processes and artifacts. The results indicate a positive impact in the short and medium term strategies and management of the startup. However, these results cannot be generalized to other startups and should be received with caution, since this is an initial exploratory study limited to a single company.